Update on the Progress of Musashi-2 in Malignant Tumors - Yiting Niu; Tao Zhou; Yanjun Li (Frontiers in Bioscience-Landmark)
Since the discovery of the Musashi (MSI) protein, its ability to affect the mitosis of Drosophila progenitor cells has garnered significant interest among scientists. In the following 20 years, it has lived up to expectations. A substantial body of evidence has demonstrated that it is closely related to the development, metastasis, migration, and drug resistance of malignant tumors. In recent years, research on the MSI protein has advanced, and many novel viewpoints and drug resistance attempts have been derived; for example, tumor protein p53 mutations and MSI-binding proteins lead to resistance to protein arginine N-methyltransferase 5-targeted therapy in lymphoma patients. Moreover, the high expression of MSI2 in pancreatic cancer might suppress its development and progression. As a significant member of the MSI family, MSI2 is closely associated with multiple malignant tumors, including hematological disorders, common abdominal tumors, and other tumor types (e.g., glioblastoma, breast cancer). MSI2 is highly expressed in the majority of tumors and is related to a poor disease prognosis. However, its specific expression levels and regulatory mechanisms may differ based on the tumor type. This review summarizes the research progress related to MSI2 in recent years, including its occurrence, migration mechanism, and drug resistance, as well as the prospect of developing tumor immunosuppressants and biomarkers.